The Conflict between Self and the Other in Mourid Barghouti’s “Ra’yat Ram Allah” - Rakhshandehnia, Seyede Akram (Al-Adab Journal, 2018)
Mourid Barghouti is among the Palestinian novelists who have lived outside Palestine and have been deprived of returning to their country for around thirty years. In his novel “Ra’yat Ram Allah” that is considered his biography he pictures Palestinian self in conflict with the Israeli other. Each of them, self and the other, include features and characteristics related to their own.This novel considers Palestinian self (I) as one of the involved parties and the Israeli other that deals with occupation and violence against Palestinian self. Considering the presence of conflict between self and the other, the Palestinian self is about to know the other and reveal his features and identity.Consequently, this research is about to study the images of Palestinian and Israeli in the light of self and the other conflict by using descriptive-analytic approach. Among the results of this research is that the writer has dealt with Palestinian self more than the other and portraits the Palestinian self’s raison d'être, be it positive or negative. And when referring to the Palestinian other he refers to occupation and colonialism characteristics more than anything.